1996
DOI: 10.1002/pc.10674
|View full text |Cite
|
Sign up to set email alerts
|

Phthalonitrile‐carbon fiber composites

Abstract: Phthalonitrile polymers offer promise as matrix materials for advanced composite applications. The phthalonitrile monomer is readily converted to a highly crosslinked thermosetting polymer in the presence of thermally stable organic amine catalysts. Rheometric studies were conducted to elucidate the optimum amine concentration for composite formulations. High quality composite panels were processed in an autoclave using unsized IM7 carbon fibers. Mechanical properties of the phthalonitrile/carbon composite are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
143
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(149 citation statements)
references
References 12 publications
4
143
0
1
Order By: Relevance
“…Phthalonitrile resin, first developed by the U.S Naval Research Laboratory and further designated as the only candidate to satisfy the flame standards of the United States Navy (MIL-STD-2031) [2], shows exceptional properties superior in many ways to other high performance thermosets such as polyimide [3] and polybenzoxazine [4].…”
Section: Introductionmentioning
confidence: 99%
“…Phthalonitrile resin, first developed by the U.S Naval Research Laboratory and further designated as the only candidate to satisfy the flame standards of the United States Navy (MIL-STD-2031) [2], shows exceptional properties superior in many ways to other high performance thermosets such as polyimide [3] and polybenzoxazine [4].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum amount of water absorbed over this time period were approximately 3.24 and 6.89% by weight for Resin-1 and Resin-2, respectively, which were relatively higher than PN cured by aromatic diamine [1]. The result indicated that the content of [EPy]BF 4 , as a kind of ILs easy to absorb water, has an influence on the water absorption of resulting resins. So we may be able to limit the water absorption capabilities of PN resins by changing the mass ratio of ILs or choosing some ILs that have higher hydrophobicity, e.g.…”
Section: Long-term Aging and Water Absorption Capabilitymentioning
confidence: 63%
“…These excellent high-temperature properties make the PN resins attractive for many military and civilian advanced technological applications, such as composite matrices [3,4], adhesives [5], electrical conductors [6], and carbon precursors [7]. However, the polymerization of neat PN compound is extremely sluggish, the high curing-temperature of PN resins limited their further applications [1].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of these materials is their high processability, and can be cured without evolution of volatiles and high char yields. 1,2 One disadvantage of the current commercial acetylene-based organic polymers is its low thermal stability, generally being limited to be used with temperature below 3008C. One practical approach to improve the thermal stability of the material is to incorporate inorganic elements such as silicon into the acetylene resins.…”
Section: Introductionmentioning
confidence: 99%